Produção e caracterização de IgY contra rLipL32 de Leptospira interrogans - Diniz, Juliana Alcoforado (2012)
Leptospirosis is a zoonosis caused by bacteria of the Leptospira genus. In recent years, efforts to identify immunogenic components of leptospires have resulted in the characterization of several outer membrane lipoproteins that are expressed during infection. Previously, our group had produced polyclonal IgY antibodies against whole-cell leptospires strain Fiocruz L1-130, which were used in different forms of capture ELISAs. In this study we produced and characterized IgY antibodies against LipL32 in recombinant form (rLipL32), the most abundant lipoprotein in the proteome of pathogenic leptospires, in order to use they in diagnostic assays and prophylaxis of leptospirosis. For this, two 22-week-old hens were immunized on day 0 with rLipL32 and oil adjuvant by intramuscular route. Three booster immunizations on days 14, 28 and 42 were held, and the eggs were collected daily from day 45. The yolks were processed and the antibodies purified with polyethylene glycol, and monitored by SDS-PAGE. Specificity of purified antibodies was assessed through indirect ELISA and Western blot (WB) using both rLipL32 and whole-cell Fiocruz L1-130. After standardization of the first batch of IgY, antibodies were conjugated with horseradish peroxidase and fluorescein (FITC). In addition, we conducted a passive immunoprotection assay in hamster model, using homologous and heterologous challenge. SDS-PAGE confirmed the successful purification of IgY and a batch with a concentration of 13μg.μL-1 was stored at -20ºC until use. Both IgY and IgY conjugated with horseradish peroxidase recognized the recombinant and native protein in ELISA and WB. In this study we produced and characterized successfully IgY against rLipL32. Although these antibodies have not been tested with clinical samples from humans or animals, they have antigen detecting potential for use in the diagnosis of leptospirosis.